Elaboración de un néctar a partir de jackfruit (Artocarpus heterophyllus) con mucílago de cacao (Theobroma cacao L.) y su mejoramiento en las propiedades organolépticas - Guaquipana Estrella, Estefania Magali (2025)
The present research focused on the elaboration of a nectar from jackfruit (Artocarpus heterophyllus) with cocoa mucilage (Theobroma cacao L.) and the evaluation of its physical-chemical and organoleptic properties, at the Soil Laboratory of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, using raw materials from the “3 Hermanos” farm, Vinces canton, Los Ríos province. The main objective was to elaborate and evaluate a nectar combining these raw materials, evaluating their physical-chemical and organoleptic characteristics to identify the most acceptable formulation. A completely randomized design was implemented with four treatments (T0: 0 %, T1: 5 %, T2: 10 %, T3: 15 % cocoa mucilage), following a process that included selection, reception, washing, disinfection, extraction, preparation, pasteurization, packaging, sterilization and refrigeration. The analyses performed covered physicochemical parameters (pH according to NTE INEN 0389.2013, titratable acidity according to INEN 381, °Brix according to INEN 380) and organoleptic characteristics (Flavor, Color, Aroma and Texture), evaluated by untrained tasters, using a 5-point hedonic scale. The research responds to the growing demand for natural functional beverages and seeks to make efficient use of agricultural by-products, especially cocoa mucilage, which is usually discarded during the processing, thus contributing to the development of value-added alternatives for the Ecuadorian agroindustrial sector.